EFEKTIVITAS LATIHAN SIRKUIT UNTUK MENINGKATKAN KEMAMPUAN BIOMOTOR ATLET BOLABASKET KU 16 TAHUN - Risa Herdiyana Bastian; Syifa Nurbait; Nur Mahfuzah Agustin (Journal of Physical Education and Sport Science, 2019)
The purpose of this study was to determine and test a circuit training method designed to improve the biomotor components of basketball athletes in the 16 year age group. The research method used in this research is an experimental method, with a 2x2 factorial design. The subjects in this study were basketball athletes aged 16 years in the city of Cirebon, who have been training for two years and have participated in regional championships. Preliminary test and final test research data were obtained from the results of treatment in the form of circuit training, for 6 weeks, 18 meetings, 3 meetings a week. The result of this study is that circuit training can effectively improve the biomotor components of basketball athletes aged 16 years.The purpose of this research is to find out: "The Effect of Sport Massage on Anxiety Before Facing Match Test on Athletes Pencak Silat STKIP Muhammadiyah Kuningan Facing Match Test. This research method is an experimental method with one-group pretest-postest design research design. The samples used were 15 athletes of Pencak Silat STKIP Muhammadiyah Kuningan. The results of the study obtained by researchers from the calculation of T paired test samples explained that there is an influence of sports massage on anxiety before facing the match test